2020
DOI: 10.1063/5.0019913
|View full text |Cite
|
Sign up to set email alerts
|

Cathodoluminescence in single and multiwall WS2 nanotubes: Evidence for quantum confinement and strain effect

Abstract: For nanoparticles with sub-10 nm diameter, the electronic bandgap becomes size dependent due to quantum confinement; this, in turn, affects their electro-optical properties. Thereby, MoS 2 and WS 2 monolayers acquire luminescent capability, due to the confinement-induced indirect-to-direct bandgap transition. Rolling up of individual layers results in single wall inorganic nanotubes (SWINTs). Up to the present study, their luminescence properties were expected to be auspicious but were limited to theoretical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 51 publications
(112 reference statements)
0
18
2
Order By: Relevance
“…Furthermore, the folding energy of WS 2 and MoS 2 plane is about 10 times larger than that of the graphitic layers into carbon nanotubes . To comply with the large elastic energy of folding, WS 2 (MoS 2 ) nanotubes adopt larger radii than their carbon counterparts and generally come in multiwall structures; however, single-walled WS 2 nanotubes were generated by high energy plasma radiation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the folding energy of WS 2 and MoS 2 plane is about 10 times larger than that of the graphitic layers into carbon nanotubes . To comply with the large elastic energy of folding, WS 2 (MoS 2 ) nanotubes adopt larger radii than their carbon counterparts and generally come in multiwall structures; however, single-walled WS 2 nanotubes were generated by high energy plasma radiation …”
Section: Introductionmentioning
confidence: 99%
“…6 To comply with the large elastic energy of folding, WS 2 (MoS 2 ) nanotubes adopt larger radii than their carbon counterparts and generally come in multiwall structures; 5 however, single-walled WS 2 nanotubes were generated by high energy plasma radiation. 7 Several chemical strategies were conceived to facilitate the folding of the layers and form pure phases of nanotubes from inorganic layered compounds. One important strategy is nanotemplating.…”
Section: ■ Introductionmentioning
confidence: 99%
“…39 In a recent study, cathodoluminescence (CL) of single-and multiwall WS 2 nanotubes was investigated. 40 While the CL signal at room temperature was extremely weak and marred by the noise, strong spectrally resolved CL was obtained at −140 °C. Clear blue shifts of the spectral features associated with the A and B excitons were observed in the singlewall tubes compared to multiwall nanotubes.…”
Section: Introductionmentioning
confidence: 95%
“…Strong light–matter coupling was also observed in ∼60 nm thick WS 2 nanodisks . In a recent study, cathodoluminescence (CL) of single- and multiwall WS 2 nanotubes was investigated . While the CL signal at room temperature was extremely weak and marred by the noise, strong spectrally resolved CL was obtained at −140 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include nanoflakes, nanosheets, nanohoneycombs, nanotubes, and nanoflowers of WS 2 to enhance the performance of energy storage devices, specifically lithium-ion batteries (LIBs). Unique structures of WS 2 have rarely been studied for sodium-ion batteries (NIBs). , Although their counterparts, namely MoS 2 nanotubes, have been extensively studied for electrochemical energy storage, electrochemical hydrogen storage, and used as field effect transistors, up-to-date WS 2 nanotubes (WS 2 NTs) have only been studied in LIBs and NIBs to a muchlesser extent, even though they establish stable cycling over a wide voltage range. ,, Theoretical calculations indicated that single-wall WS 2 NTs are an exclusive type of semiconductor with an explicit band gap ranging from 0.1 to 1.9 eV, depending on their diameter. , They become both direct (in the case of a zigzag) and indirect (in the case of an armchair) band gap semiconductors controlled by chirality, making them useful for various technological applications such as next-generation electronic and optoelectronic devices and high-quality factor nanoelectromechanical systems. , However, the electronic properties of multiwall WS 2 NTs, which are currently produced in large amounts, are not that different from those of the bulk material, that is, having an indirect band gap of ∼1.9 eV . Such a small bandgap make them suitable for the next generation electrochemical energy storage devices.…”
Section: Introductionmentioning
confidence: 99%